Analisis Perkembangan Ekonomi Syariah Di Asia Tenggara Pasca Berdirinya BRICS - Kayla Revina Nurmaulidia; Listari, Sarita Putri; Aulia, Yoanda Vani; Rosyada, Amrina; Febriani, Mila (Journal of Economics and Business, 2024)
ABSTRACT This article analyzes the development of Islamic economics in Southeast Asia following the establishment of BRICS, a group of emerging economies consisting of Brazil, Russia, India, China, and South Africa. Since its formation, BRICS has significantly impacted the global economy, including the Islamic finance sector. Southeast Asian countries, such as Indonesia and Malaysia, have leveraged this opportunity to strengthen the development of Islamic economic sectors, especially in Islamic banking, Islamic capital markets, and the halal industry. Despite challenges related to education, regulation, and financial inclusion, Southeast Asian countries have great potential to lead the global Islamic economy sector. This article also discusses the opportunities for cooperation with BRICS nations and how the Islamic economic sector can grow through stronger international relations. The study concludes that with the right policies and international collaboration, Islamic economics in Southeast Asia can continue to grow and contribute positively to a globally inclusive and sustainable economy.   ABSTRAK Artikel ini menganalisis perkembangan ekonomi syariah di Asia Tenggara pasca berdirinya BRICS, sebuah kelompok negara berkembang yang terdiri dari Brasil, Rusia, India, Cina, dan Afrika Selatan. Sejak pembentukannya, BRICS telah memberikan dampak signifikan terhadap ekonomi global, termasuk sektor keuangan syariah. Negara-negara di Asia Tenggara, seperti Indonesia dan Malaysia, telah memanfaatkan peluang ini untuk memperkuat pengembangan sektor ekonomi syariah, terutama dalam bidang perbankan syariah, pasar modal syariah, dan industri halal. Meskipun ada tantangan terkait edukasi, regulasi, dan inklusi keuangan, negara-negara Asia Tenggara memiliki potensi besar untuk memimpin sektor ekonomi syariah global. Artikel ini juga membahas peluang kerja sama dengan negara-negara BRICS dan bagaimana sektor ekonomi syariah dapat berkembang melalui hubungan internasional yang lebih kuat. Penelitian ini menyimpulkan bahwa dengan kebijakan yang tepat dan kolaborasi internasional, ekonomi syariah di Asia Tenggara dapat terus berkembang dan memberikan kontribusi positif terhadap perekonomian global yang inklusif dan berkelanjutan.